Answer:
Step-by-step explanation:
Using the Translation theorem to transform the s-3 to s, that means multiplying by and change s to s+3
Translation theorem:
Separate the fraction in a sum:
The formula for this is:
Modify the expression to match the formula.
Solve
Based on the graph of the linear function (in blue) and parabolic function (in red), the corresponding output values include the following;
(f∘g)(2) = -1.
(g∘f)(2) = 1.
(f∘f)(2) = 0.
(g∘g)(2)= 4.
(f + g)(4) = 7.
(f/g)(2) = DNE.
In Mathematics and Geometry, a function composition is an operation (∘) that combines two functions f(x) and g(x), in order to produce a composite function h(x) = (g∘f)(x), such that h(x) = g.
In this exercise, we would determine the corresponding output values for each of the composite functions by using the substitution method as follows;
(f∘g)(2) = f(g(2))
f(g(2)) = f(0)
f(0) = -1.
Part 2.
(g∘f)(2) = g(f(2))
g(f(2)) = g(1)
g(1) = 1.
Part 3.
(f∘f)(2) = f(f(2))
f(f(2)) = f(1)
f(1) = 0.
Part 4.
(g∘g)(2) = g(g(2))
g(g(2)) = g(0)
g(0) = 4.
Part 5.
(f + g)(4) = f(4) + g(4)
f(4) + g(4) = 3 + 4
f(4) + g(4) = 7.
Part 6.
(f/g)(2) = f(2)/g(2)
f(2)/g(2) = 1/0
f(2)/g(2) = DNE.
Read more on composite function here: brainly.com/question/30660139
#SPJ2
Step-by-step explanation:
g(g(2))
= g(0)
= 4
the six trigonometric functions
of theta= 4pi
Step-by-step explanation:
We have,
To write the six trigonometric functions = ?
∴ The six trigonometric functions, , ,, , and .
it's simple
3t+3
just this
Step-by-step explanation:
Factor by grouping.
f(x) = x³ + 3x² − 5x − 4
f(x) = x³ + 3x² − 4x − x − 4
f(x) = x (x² + 3x − 4) − (x + 4)
f(x) = x (x − 1) (x + 4) − (x + 4)
f(x) = (x² − x) (x + 4) − (x + 4)
f(x) = (x² − x − 1) (x + 4)
Answer:
B) 74 degrees
Step-by-step explanation:
three angles = 180
2x+32=180
2x=148
x=74
Hope this helps plz hit the crown :D
Answer:
i think B which is 74
Step-by-step explanation: